Effect of Work Discipline and Loyalty on Employee Achievement of PT. Djasa Sumatra - Rini Gotama; Rusdiana Simamora (Jurnal Mantik, 2022)
PT. Djasa Sumatra is a company engaged in shipping freight forwarding services. This study aims to determine the effect of work discipline and work loyalty on the work performance of employees of PT. Djasa Sumatra. This type of research is explanatory research. The population in this study were all employees who worked at PT. Djasa Sumatra as many as 57 employees. The sampling technique used is saturated sampling. In this study, the questionnaire will be distributed as measured by a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous and partial tests. The results showed that work discipline and work loyalty partially or simultaneously had a positive and significant effect on the work performance of PT. Djasa Sumatra. Based on the results of this study, the implication for management is to further improve work discipline and work loyalty.